A Biomechanical Study of Tuberosity-Based Locked Plate Fixation Compared with Standard Proximal Humeral Locking Plate Fixation for 3-Part Proximal Humeral Fractures. Issue 7 (July 2020) - Walker, Robert; Castaneda, Paulo; Putnam, Jill G.; Schemitsch, Emil H.; McKee, Michael D.
Abstract : Background: One of the main shortcomings of current proximal humeral plate designs is their inability to reliably secure the greater tuberosity (GT) or lesser tuberosity, leading to fixation failure, nonunion, and rotator cuff dysfunction. Traditional proximal humeral locking plates (PHLPs) rely on isolated screw fixation or suture repair to maintain reduction of the greater and/or lesser tuberosities. This study evaluates a tuberosity-based plate (TBP) specifically designed to improve tuberosity fixation, which may decrease tuberosity displacement and related clinical sequelae. Methods: Five cadaveric specimens (10 shoulders) were randomized to receive either standard PHLP or TBP fixation. The specimens were skeletonized except for the rotator cuff insertion on the GT. A reproducible 3-part osteotomy was performed for each cadaver, creating head, shaft, and GT segments. Anatomic reduction and plate fixation were performed according to the surgical technique guide for each plate system, with an equal number of screws placed in each plate both proximally and distally. GT fixation was enhanced with standardized suture augmentation through the rotator cuff in every specimen in both groups. In each trial, fracture displacement, load to failure, number of cycles endured, and mechanism of failure were noted. Results: The mean load to tuberosity fixation failure for the PHLP and TBP groups was 220 and 502 N ( P = 0.005), respectively. Conclusions: The TBP had a significantly higher load to failure and significantly lower mean fracture displacement compared with the PHLP. Abstract : Supplemental Digital Content is Available in the Text.